The occupational environment : its evaluation, control and management - Anna, Daniel H.; American Industrial Hygiene Association (Fairfax, Va. : American Industrial Hygiene Association, 2011)
Meet today's critical issues and challenges as an occupational health and safety practitioner, educator, or student with the tools, methodologies and knowledge provided in this reference--Cover.
Vol. 2. Section 4: Physical Agent Recognition and Evaluation -- 24. Noise, vibration, and ultrasound -- 25. Nonionizing radiation -- 26. Ionizing radiation -- 27. Applied physiology of thermoregulation and exposure control -- 28. Thermal standards and measurement techniques -- 29. Barometric hazards -- -- Section 5: The Human Environment -- 30. Ergonomics -- 31. Musculoskeletal disorders, job evaluation, and design principles -- 32. Upper extremities -- 33. Occupational health psychology -- -- Section 6: Methods of Controlling the Work Environment -- 34. Prevention and mitigation of accidental chemical releases -- 35. General methods for the control of airborne hazards -- 36. Dilution ventilation -- 37. Local exhaust ventilation -- 38. Testing, monitoring, and troubleshooting of existing ventilation systems -- 39. Personal protective clothing -- 40. Respiratory protection -- -- Section 7: Program Management -- 41. Program management -- 42. Surveys and audits -- 43. Hazard communication -- 44. Emergency planning and crisis management in the workplace -- 45. Risk communication -- 46. Confined spaces -- 47. Industrial hygiene issues in construction -- 48. Hazardous waste management -- 49. Laboratory health and safety -- 50. Developing an occupational health program -- 51. Report writing -- 52. Occupational safety -- 53. The AIHA value strategy.
AIHI Stock Number: BIHT10-566.
Earlier eds. edited by Salvatore R. DiNardi.
Includes bibliographical references and index.
Keywords: Industrial hygiene; Occupational diseases -- Prevention; Industrial safety; Occupational Diseases -- prevention & control; Occupational Exposure -- prevention & control; Occupational Health; Safety Management -- organization & administration; Industrial hygiene; Industrial safety; Occupational diseases -- Prevention